Polymer Complexes of Ofloxacin and Their Antibacterial Activity - E. P. Ananyeva; S. S. Baranov; A. V. Karavaeva; M. S. Borisenko; M. V. Solovskiy; N. V. Zacharova; T. A. Prazdnikova; E. B. Tarabukina (Антибиотики и Химиотерапия, 2020)
To lower the toxicity and to prolong the action of the monofluoroquinolone ofloxacin, its water-soluble polymer complexes were developed. Cationic copolymers of N-vinylpyrrolidone (VP) with 2-aminoethylmethacrylate (2-AEM) and its hydrochloride (2-AEM-HCl), containing 10.9-28.3 mol. % -NH2 or -NH3Cl group with the molecular mass (MM) of 10500 to 89000 were synthesized as the complex-forming polymers. The cationic copolymers showed their own antimicrobial activity. The polymer complexes contained 18-36% of fluoroquinolone and had high antimicrobial activity against S.aureus and E.coli, that increased with an increase of the ofloxacin content in the complex and a decrease of its MM. The kinetic studies on the ofloxacin release from its polymer complex with MM of 60000, containing 36% of fluoroquinolone revealed prolongation of the medicinal substance release from the complex in the buffer solution at pH 2.0 and a temperature of 37°C. The acute toxicity tests on mice with intraperitoneal administration of ofloxacin and copolymer VP containing 20.8 mol. % -NH3Cl group (MM of 51000) s